Answer:
- 13 - 23 = - 13 + (-23)
= -36
- 13 - (- 23) = - 13 + 23
= 10
Explanation:
In any order of operation (i.e. addition, subtraction, multiplication, devision) the following rules apply for two values for instance a and b where a > b :
→ If +a and +b then the final sign will be + (positive)
→ If +a and -b then the final sign will be + (positive) since a>b
→ If -a and +b then the final sign will be - (negative) since a>b
→ If -a and -b then the final sign will be - (negative)
In the given question we have two cases.
Case 1:
- 13 - 23 = - 13 + (-23) → since it is given that we add a negative value of -23, therefore it keeps its sign (so this would be a negative addition i.e. adding two negative values)
Thus we have:
- 13 - 23 = - 13 + (-23)
= -36
Case 2:
- 13 - (- 23) = - 13 + 23 → since we stated earlier that - and - gives positive sign (i.e. we subtract two negative values)
Thus we have:
- 13 - (- 23) = - 13 + 23
= 10
So we can see that:
Adding two Negative values gives a Negative value (Case 1)
Subtracting two Negative values gives a Positive value (Case 2)